Seroprevalence and Associated Factors of HBV and HCV among Pregnant Women Attending Antenatal Care at Debre Tabor Comprehensive Specialized Hospital, Northwest Ethiopia: A Cross-Sectional Study - Assefa, Ayenew; Kiros, Teklehaimanot; Delelegn, Birtukan (International Journal of Microbiology, 2023)
Background. Infections with the hepatitis B virus (HBV) and the hepatitis C virus (HCV) are worldwide problems that particularly place a heavy burden on developing nations. HBV and HCV infections during pregnancy have a high rate of vertical transmission and harmful consequences for both the mother and the child. Therefore, this study was carried out to assess the seroprevalence and associated factors of HBV and HCV infections among pregnant women attending antenatal care at Debre Tabor Comprehensive Specialized Hospital in Ethiopia. Methods. A cross-sectional study was conducted from March 15th to September 16th, 2022, at the Debre Tabor Comprehensive Specialized Hospital antenatal care clinic. Five milliliters of venous blood were collected from 422 pregnant women selected using a simple random sampling method. Data on sociodemographic characteristics and risk factors were collected using a prestructured questionnaire. A chi-square test, bivariate, and multivariate analyses were used to evaluate the association between dependent and independent variables. p values less than 0.05 were considered statistically significant. Results. The seroprevalence of HBV and HCV infections was found to be 13% and 0.5%, respectively. Undertaking blood transfusion (AOR = 14.2, CI = 5.81–34.526, p=0.001), tattooing (AOR = 3.99, CI = 1.1–14.36, p=0.034), and dental therapy (AOR = 4.9, CI = 1.41–17.025, p=0.012) were significantly associated with HBV infection. Conclusion. HBV infection in pregnant women was shown to have a high endemicity (13%) in this investigation, whereas the seroprevalence of HCV infection was low (0.5%). HBV infection was significantly associated with a history of blood transfusions, tattooing, and dental therapy. Screening pregnant women for HBV and HCV infections and providing effective therapy would ensure better outcomes for the newborn. In addition, health education must be used to increase knowledge of screening and modes of transmission.